On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species, complementary descriptions and new records (Araneae: Salticidae) - Estol, Narelle; Marta, Kimberly S.; Rodrigues, Everton Nei Lopes (Zootaxa, 2020)
The genus Tullgrenella Mello-Leitão, 1941 presently consists of 13 exclusively Neotropical species. In this paper both sexes of two new species are described from Bolivia: Tullgrenella nadjae sp. nov. and Tullgrenella brescoviti sp. nov. The female of T. guayapae Galiano, 1970 is described and illustrated for the first time. Additionally, new records from southern Brazil are provided for T. guayapae, T. serrana Galiano, 1970, T. quadripunctata (Mello-Leitão, 1944) and T. yungae Galiano, 1970.